PENGUKURAN KINERJA INSTALASI FARMASI RSUD DATOE BINANGKANG KABUPATEN BOLAANG MONGONDOW DENGAN METODE BALANCED SCORECARD - Laleno, Ellysa N.; Citraningtyas, Gayatri; Rumondor, Erladys M. (PHARMACON, 2020)
ABSTRACTPerformance measurement used the Balanced Scorecard method needs to be done at Datoe Binangkang Hospital General Pharmacy Installation to measure the performance achievements that have been carried out by Datoe Binangkang Hospital General Pharmacy Installation and as a basis for further performance improvement. This research aims to determine the performance of IFRS Datoe Binangkang with the Balanced Scorecard method in terms of the financial perspective and the perspective of internal business processes. This research is descriptive used a retrospective approach to financial perspective and prospective for internal business processes. Primary data were obtained from direct observation and secondary data were obtained from IFRS financial administration reports and Datoe Binangkang District Hospital. The results showed that in the financial perspective of 2019: the contribution of IFRS to RSUD 73.01%, ITOR 3.65 times and the average age of inventor 100 days. Internal business perspective: The level of availability of drugs is 95%, the average dispensing time for non-concoction prescriptions is 22.17 minutes and prescription concoctions at IFRS that are usually given to children, replaced with drugs that are already available according to the patient's illness, the component of drug information given to patients still does not meet the standards set by the Indonesian Minister of Health  No. 73 of 2016. The conclusion is the performance of Datoe Binangkang Hospital Pharmacy Installation is quite good, but needs to be improved in terms of drug inventory control, dispensing time and drug information services. Key words: Performance, Pharmacy Installation Datoe Binangkang District Hospital, Balanced ScorecardABSTRAK Pengukuran kinerja dengan metode Balanced Scorecard perlu dilakukan di Instalasi Farmasi RSUD Datoe Binangkang untuk mengukur pencapaian kinerja yang telah dilakukan Instalasi Farmasi RSUD Datoe Binangkang serta sebagai dasar untuk perbaikan kinerja selanjutnya. Penelitian ini bertujuan untuk mengetahui kinerja IFRS Datoe Binangkang dengan metode Balanced Scorecard ditinjau dari perspektif keuangan dan perspektif proses bisnis internal. Penelitian ini bersifat deskriptif dengan menggunakan pendekatan retrospektif untuk perspektif keuangan dan prospektif untuk proses bisnis internal. Data primer diperoleh dari observasi langsung, wawancara dan data sekunder diperoleh dari laporan administrasi keuangan IFRS dan RSUD Datoe Binangkang. Hasil penelitian menunjukan bahwa pada perspektif keuangan tahun 2019: kontribusi IFRS ke RSUD 73,01%, ITOR 3,65 kali dan average age of inventory 100 hari. Perspektif bisnis internal: Tingkat ketersediaan obat 95%, average dispensing time untuk resep non-racikan 22,17 menit dan resep racikan di IFRS yang biasanya diberikan pada anak, diganti dengan obat-obatan yang sudah tersedia sesuai dengan penyakit yang diderita pasien, komponen informasi obat yang diberikan kepada pasien masih belum memenuhi standar yang telah ditetapkan oleh Permenkes RI No. 73 Tahun 2016. Kesimpulannya yaitu kinerja Instalasi Farmasi RSUD Datoe Binangkang sudah cukup baik, akan tetapi perlu dilakukan perbaikan dalam hal pengendalian persediaan obat, dispensing time dan pelayanan informasi obat. Kata kunci : Kinerja, Instalasi Farmasi RSUD Datoe Binangkang, Balanced  Scorecard